Decreased Physical Activity Predicts Cognitive Dysfunction and Reduced Cerebral Blood Flow in Heart Failure - Alosco, Michael L. (2014)
OBJECTIVE: Cognitive impairment in heart failure (HF) is believed to result from brain hypoperfusion subsequent to cardiac dysfunction. Physical inactivity is prevalent in HF and correlated with reduced cardiac and cognitive function. Yet, no longitudinal studies have examined the neurocognitive effects of physical inactivity in HF. The current study examined whether reduced physical activity increases risk for cognitive impairment and brain hypoperfusion over time in HF. METHODS: At baseline and 12-months later, 65 HF patients underwent neuropsychological testing, transcranial doppler ultrasonography, and were asked to wear an accelerometer for seven days. RESULTS: Lower baseline step count and less time spent in moderate free-living activity best predicted worse attention/executive function and decreased cerebral perfusion at the 12-month follow-up. Decreased baseline cerebral perfusion also emerged as a strong predictor of poorer 12-month attention/executive function. CONCLUSIONS: Lower physical activity predicted worse cognition and cerebral perfusion 12-months later in HF. Physical inactivity in HF may contribute to cognitive impairment and exacerbate risk for conditions such as Alzheimer’s disease. Larger studies are needed to elucidate the mechanisms by which physical inactivity leads to cognitive dysfunction in HF, including clarification of the role of cerebral hypoperfusion.